Design and Implementation of Protection Relay 3 Phase Induction Motor - Kukuh Widarsono; Abdillah Fashiha Ilman; Alfian Rejeki (Department of Electrical Engineering ITS and FORTEI, 2019)
Damage to the electrical components will inevitably occur, it could be caused by several factors that influence it starting from inside and outside the system. 3 phase induction motor is the most commonly used in the industry, but often also has problems such as over current and over heat on the motor. The disturbance if left unchecked can cause fatal damage to the motor. therefore, a relay safety system has been made which utilizes a microcontroller controller to protect the 3 phase induction motors. This safety relay is designed differently than conventional safety relays used by industry in general, this safety relay is designed based on the microcontroller control and is accompanied by setting and resset facilities respectively to display on the LCD via Push Botton buttons. As such, 3 phase induction motors are protected from severe damage caused by interference with the mesh source. It is expected that by making this safety relay can reduce the value of damage to the 3 phase induction motor.Keywords: microcontroller, overcurrent, overheat, three phase induction motor.